Winning innovation : how innovation excellence propels an industry icon toward sustained prosperity - Majerus, Norbert; Taninecz, George (Productivity Press, 2022)
Testa Della Corsa, an Italian bicycle company, makes the best racing bikes in the world. But after decades of market dominance, competitors have brought the industry leader back to the peloton. The company⁰́₉s second-generation owner longs for retirement, but a tired product lineup is pushing down profits and the firm⁰́₉s market value will never support his ride into the sunset. The flawed but beloved owner seeks out the counsel of an old friend and successful businessman, who steers him toward a fast and remarkable transformation, one fueled by a relentless focus on innovation excellence. An engaging business novel, Winning Innovation dives into the art and science of innovation; the thrills of the European bike-racing circuit; the vibrant landscape and cuisine of Italy; and a cast of intriguing characters who work to put Testa on the road to sustained prosperity. The company⁰́₉s leader isn⁰́₉t afraid to learn and apply new ideas to re-energize his company and finds he cares more about his employees than he could ever imagine. A young innovator struggles to see a product idea to fruition as well as rise into management ⁰́₄ and he falls in love along the way. A newly promoted R&D director brings teamwork and transparency to product development and aligns the entire company around innovation. With the help of a seasoned and persistent change agent, in just a year Testa deploys a well-defined and -sequenced transformation ⁰́₄ a complete and seamless process that can be replicated and scaled by most companies. The leader engages associates in pursuit of the right vision and strategy, candidly supporting them all as they unleash their creative sparks, work through personality conflicts, and take on real-world challenges faced by companies every day. They learn and apply traditional R&D principles in new ways (e.g., cost of delay, sprints, fail fast, late start) and successfully leverage emerging innovation and change-management principles (e.g., idea-creation events, knowledge management, workplace humility, visual management, lean project management). And an aligned, three-phase innovation process ⁰́₄ from idea creation to technology development and product design ⁰́₄ provides the innovation infrastructure the company needs for revenue creation and success beyond racing bikes. From a top-heavy organization dominated by power struggles and fingerpointing emerges a new Testa Della Corsa ⁰́₄ a flattened, innovative company with: ⁰́Ø Clear vision and endorsed goals and strategy ⁰́Ø Speed, responsiveness, and agility ⁰́Ø Widespread, successful creativity ⁰́Ø Collaboration and teamwork ⁰́Ø Superior risk management ⁰́Ø Respect for people ⁰́Ø Unquestionable ethics ⁰́Ø Changed leadership and associate behaviors ⁰́Ø Project management excellence, and ⁰́Ø Rapid problem-solving and experimentation. Not just the story of an R&D transformation, Winning Innovation illustrates a companywide transformation of a magnitude that only superior R&D can make possible. It may well be the first book to chronologically introduce the principles for a complete innovation excellence transformation along with the parallel people transformation that is necessary for real change to occur. The end result for Testa Della Corsa is a dominant new culture based on respect and humility; highly efficient processes that will deliver a wealth of innovations, sales, and profits for many years to come; and an owner who leaves a bright future for the people and company he⁰́₉s known and loved his entire life.